Altered pulmonary functions due to biomass smoke in a rural population of Turkish women: a descriptive study - CEYHAN, BERRİN; BALCAN, MEHMET BARAN (TURKISH ASSOC TUBERCULOSIS & THORAX, 2018)
Introduction: Wood or other organic sources of fuel are used as source of energy for heating or cooking particularly in developing countries. The aim of the current study was to evaluate the association between biomass exposure time and parameters of pulmonary function tests. Materials and Methods: Four hundred twenty-four consecutive women who lived and exposed to biomass smoke in a small province in Eastern Turkey were involved. This study was performed with women who had come to pulmonology out-patient clinic with symptom of dyspnea. Results: The independent variables assessed in the study patients were age, BMI, starting age of cooking, hours per day and weeks per month spent cooking, and cooking years; the dependent variables were PFT parameters. Ninety-two (21.6%) patients had an obstructive PFT pattern. Sixty-seven (73%) of these patients were classified as GOLD 2 and 25 (27%) patients were classified as GOLD 3. Seventy-five (17.6 %) of the patients had restrictive lung disease; 54 (72%) of these patients were found to have a mild and 21 (27%) had a moderate restrictive pattern. Increased number of years in cooking and to start cooking at younger ages were a risk factors for the development of obstructive and restrictive disease. There was a statistically significant and negative correlation between increased number of years and the value of FEV1 (r=-0.917; p=<0.001), FEV1/FVC (r=-0.739; p<0.001), and FVC (r=-0.906; p<0.001). The median time of cooking required was 23 years for the development of obstruction, and 25 years for restriction, respectively. Conclusion: Cumulative biomass exposure time is associated with impairment in PFT parameters; results in both obstructive and restrictive lung disease. Biomass exposure is a public health problem and pre-cautions should be taken in order to prevent impaired pulmonary functions.
Keywords: Biomass; pulmonary function testing; exposure; INDOOR AIR-POLLUTION; EXPOSURE; DISEASE; COPD; FUEL; HEALTH; PREVALENCE; CHILDREN; RISK